Socio-ecological analysis of the eutrophication in Chesapeake Bay, USA - Leyva Ollivier, María Esther; Newton, Alice; Kelsey, Heath (Frontiers in Marine Science, 2023)
This study is a social-ecological analysis of eutrophication in the Chesapeake Bay, United States of America (USA). It uses an expanded DPSIR framework (Drivers Pressures, State, Impacts Responses) methodology to analyze the issue. In addition, a typology of the social actors and stakeholders in the socio-economic part of the system is identified. These include residents, agriculturists, fishers, real estate developers, tourism operators, scientific researchers, and state and federal regulators. The Drivers are food security, housing, economic development, recreation pursuits, a sense of belonging, and population growth. These result in human Activities such as land and coastal change for development, coastline changes for fisheries, urban or suburban development, burning fossil fuels, and agricultural fertilization. The activities exert Pressures such as wastewater discharge, runoff from cleared land, atmospheric deposition (NOx), nutrient input, decreased tidal vegetation, and overfishing of filter feeders. These alterations change the State of the environment and its resilience by increasing the duration and areal extent of hypoxia, turbidity, and change in nutrient ratios. This also causes ecosystem changes, such as decrease of wildlife diversity and affects the ecosystem services, such as decreasing nutrient buffering. The health of Chesapeake Bay benefits all stakeholders and wildlife, so the reduction of ecosystem services results in Impacts on society's welfare and well-being, the economy, and environmental justice. Examples are decreased yields from fisheries, poorer water quality affecting aesthetics, tourism, and ultimately human health. The governance Response to the degradation of the Chesapeake Bay and main management Measures has been the creation of the Chesapeake Bay Watershed Agreement (CBWA) by the Chesapeake Bay Program, which implemented the Total Maximum Daily Load (TMDL) to meet quality standards. The Agreement also has the Best Management Practices (BMP), which regulate the point/nonpoint sources of nutrients around the Watershed. The Chesapeake Bay Foundation (CBF), Chesapeake Progress, and Report Cards are used as accountability tools to observe and communicate the management project results or enforce state laws. The current management shows promising results, but further efforts are required to improve the water quality. Using a range of management options may bridge this gap to the benefit of all stakeholders.